Investigating physical fitness and race performance as determinants for the ACL injury risk in Alpine ski racing - Schmitt, K. U.; Hörterer, N.; Vogt, M.; Frey, W. O.; Lorenzetti, S. (BMC Sports Science, Medicine and Rehabilitation, 2016)
ACL ruptures in Alpine ski racers are frequently observed. This study analysed the association between physical fitness, race performance and the knee injury history. Methods: A retrospective study was conducted to investigate the influence of physical fitness and performance on the knee injury outcome. As part of this study an injury data base (covering 2004-2013) was established that recorded information about the athletes, their fitness status as determined by a standardised fitness test (Swiss Ski Power Test, SSPT) as well as medical information related to injuries. The performance of athletes who sustained knee injury was compared to athletes who suffered no injury or a different injury. Results: Twenty-seven (19f, 8 m) of 70 athletes sustained a knee injury. ACL ruptures accounted for 71 % of these knee injuries. While more females sustained a knee injury, the difference between males and females was not statistically significant. It was shown that athletes with a better FIS (Fédération Internationale de Ski) rank were more prone to knee injury. However, none of the parameters related to physical fitness was linked to a history of knee injury. Conclusions: A general fitness test as SSPT is not associated with a history of knee injury in Alpine skiing. More specific physical fitness test procedures should be investigated to determine relevant fitness factors.